2006
DOI: 10.1007/s00330-006-0195-4
|View full text |Cite
|
Sign up to set email alerts
|

Higher sensitivity in the detection of inflammatory brain lesions in patients with clinically isolated syndromes suggestive of multiple sclerosis using high field MRI: an intraindividual comparison of 1.5 T with 3.0 T

Abstract: The purpose of this study was to determine the sensitivities in the detection of inflammatory lesions in patients with clinically isolated syndromes suggestive of multiple sclerosis at 3.0 T and 1.5 T. MR imaging of 40 patients at both field strengths was performed in separate sessions including contiguous axial slices of T2 turbo spin-echo (T2 TSE), fluid-attenuated-inversion-recovery (FLAIR) and pre- and postcontrast T1 spin-echo (T1 SE). Inflammatory lesions > 3 mm in size were counted and categorized accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 31 publications
1
60
0
Order By: Relevance
“…The detailed MR imaging parameters have been described previously. 28,36 We performed all sequences in an identical anatomic position. The scan orientation and repositioning was performed according to the guidelines of the Consortium of MS Centers.…”
Section: Mr Imaging Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed MR imaging parameters have been described previously. 28,36 We performed all sequences in an identical anatomic position. The scan orientation and repositioning was performed according to the guidelines of the Consortium of MS Centers.…”
Section: Mr Imaging Protocolmentioning
confidence: 99%
“…26 At greater magnetic fields, conventional MR imaging provides higher sensitivities in the detection of inflammatory brain lesions, and 1 H-MR spectroscopy is likely to be more sensitive in the quantification of brain metabolites because of increased signal intensity and improved spectral separation. [27][28][29][30][31] In particular, at 1.5T there is still considerable overlap of the signals from the C1-C3 and C4 -C6 protons of mIns, with the CH triplet components of Glx centered at 3.76 ppm, whereas at 3T these 2 mIns multiplets appear as a pseudodoublet at 3.54 ppm and 3.62 ppm, well separated from the Glx resonances. Therefore, the step from 1.5T to 3T is also associated with a marked alteration in the MR spectral pattern of mIns, and improved quantification accuracy for mIns has indeed been observed at 3T.…”
mentioning
confidence: 99%
“…42 Furthermore, the linear registration method used to warp the lesion masks of individual patients to the template, by definition, cannot correct for the variability in ventricular and sulcal sizes that is present in patients with MS as a result of differences in brain atrophy. Therefore, the matching between individual patients' brains will be imperfect; this discrepancy leads to less accurate overlay of corresponding anatomic areas and may explain, to some extent, why we only found clusters in the periventricular region and not in areas with a lower lesion frequency.…”
Section: Discussionmentioning
confidence: 99%
“…The first evidence that the new high field MRI generation provides higher lesion load measurements in MS patients was brought up by an intraindividual comparative study between 1.5 and 4 T. Keiper et al showed a 45% increase of T2 lesions using a 4-T compared to a 1.5-T scanner [25]. This higher sensitivity in the detection of focal MS lesions and/or lesion volumes could be conclusively confirmed by the subsequent studies comparing field strengths between 1.5 and 3 T including a total number 115 patients scanned with MRI scanners of three different vendors [26][27][28][29]. The increase in lesion numbers on T2/fluid-attenuated inversion recovery (FLAIR) images ranged from 13% to 41.6%.…”
Section: Conventional High Field Mri At 3 T In Multiple Sclerosismentioning
confidence: 90%
“…The authors found a pronounced increase of T2 and FLAIR lesion numbers in anatomic regions which are important for the diagnosis of MS within diagnostic criteria and prognostic purposes in terms of prediction of long-term disability, namely in the juxtacortical, periventricular, and of course in the infratentorial region ( Fig. 1) [27]. Further analysis revealed that based on a multisequence protocol including a Gd-enhanced T1-weighted sequence, 27.5% of those patients with more lesions on the 3 T fulfilled one additional MRI criterion [30].…”
Section: Conventional High Field Mri At 3 T In Multiple Sclerosismentioning
confidence: 95%